Using a Microsimulation of Energy Balance to Explore the Influence of Prenatal Sugar‐Sweetened Beverage Intake on Child BMI. Issue 4 (22nd February 2021) - Kasman, Matt; Heuberger, Benjamin; Mack‐Crane, William; Purcell, Rob; Hammond, Ross A.; Oken, Emily; Kleinman, Ken P.
Abstract : Objective: Experiments with animals suggest that high sugar consumption during pregnancy may predispose offspring to obesity, but few human studies have examined this relationship. This study explored the association between the consumption of sugar‐sweetened beverages (SSBs) during pregnancy and caloric intake through childhood. Methods: Using cohort data on child weight, height, and physical activity levels, a lab‐validated microsimulation model of energy balance was employed to infer the caloric intake of children through age 11 years. Random effects models were then employed to explore the relationships between prenatal maternal consumption and inferred caloric intake during childhood. Results: An additional daily serving of SSBs during the second trimester of pregnancy was associated with an increase in child consumption of 13 kcal/d (95% CI: 1.2‐26.8). Age‐stratified models adjusting for maternal and child covariates suggested that this association was strongest for children aged 2.5 to 5.5 years. The consumption of SSBs during the first trimester was not found to have a consistently positive relationship to caloric intake. Conclusions: These findings suggest that SSB consumption during the second trimester of pregnancy is associated with child energy intake and may influence anthropometry in early childhood, which is consistent with and suggestive of the presence of biological causal pathways alongside likely simultaneous contributions of social and environmental influences.